Analytical Method to Estimate Railroad Spike Fastener Stress. Issue 11 (November 2020) - Dersch, Marcus S.; Silva, Matheus Trizotto; Edwards, J. Riley; Lima, Arthur de O; Roadcap, Tom
Previous research indicates that spike fastener fatigue failures have led to at least ten derailments since 2000. Given that railroads continue to install fastening systems that have experienced spike failures, methods to quantify the stress state of the spike must be developed. Common approaches to quantify the effect of key variables include laboratory experimentation, field instrumentation, or finite element model development. However, these approaches may be both time and cost prohibitive. An analytical method based on beam on elastic foundation mechanics, similar to the analysis of laterally loaded piles in deep foundation design, was developed to estimate the spike stresses. The outcome is a laboratory-validated analytical approach that generates estimates of spike stress. This analytical model was used to investigate key design criteria (timber modulus, spike cross-sectional area, and load applied) that could be changed to improve the resiliency of the fastening system to increase railroad safety. Another outcome of this study is the development of an instrumented spike that quantifies the spike demands when installed and loaded within a crosstie.